All-trans retinoic acid and genistein induce cell apoptosis in OVCAR-3 cells by increasing the P14 tumor suppressor gene - Mehdi Nikbakht Dastjerdi; Saeed Zamani; Mohammad Mardani; Batool Hashemi Beni (Wolters Kluwer Medknow Publications, 2016)
In this study, we evaluated the effects of all-trans retinoic acid (ATRA) alone or in combination with genistein (GEN) in p14 tumor suppressor gene and subsequent apoptosis of human ovarian carcinoma cells (OVCAR-3). The cells were treated with ATRA or GEN at concentrations of 50 and 25 μM respectively, either alone or in combination for 24 and 48 h. The cell viability was evaluated using 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) assay. The percentage of cell apoptosis was determined using flow cytometry and p14 gene expression was measured using real time PCR. The MTT results showed that in both ATRA and GEN treated groups, the cell viabilityviability in group treated for 48 h was significantly lower than group treated for 24 h. The flow cytometry results showed that the percentage of apoptotic cells in groups that treated with ATRA and GEN in combination for 24 h and 48 h was significantly more than all other tested groups. The real time results showed that the mRNA level of p14 in cells treated with both drugs for 48 h was significantly higher than all other groups. In conclusion, we confirm that GEN in combination with ATRA is an effective strategy to up regulate the p14 tumor suppressor gene and induce cell apoptosis in OVCAR-3 cell line.